Kekuatan Memori dan (Ketidak)Mungkinan Pengampunan dalam Novel Hanauzumi Karya Jun’ichi Watanabe - Intannia Cahyasari (POETIKA, 2017)
This study analyzes memory formation along with its transmission and forgiveness as a tool used by Gin as the main character to form the discourse of truth within the scope of society's way of thinking that has not been touched by the modernization of the Meiji Restoration era. Hanauzumi's novel implies that a bitter and tragic past can not be forgotten just by Gin. And furthermore, there is a chance redemption done by Gin by striving to realize his goal of reaching the doctor's profession as a sense of solidarity among fellow women. The purpose of this study is to present memory and forgiveness as a tool used by Gin to form the discourse of truth, thus giving him the power to fight for justice for women's rights, rights for himself and for other women. The method used in this research is descriptive qualitative. This research tries to illustrate the traumatic events of the main character who became the forerunner of his struggle to become the first female doctor in Japan.Key Words: Memory, Power, Forgiveness, Trauma, Meiji Restoration